TECHNOLOGY OF APPLICATION OF VARIOUS TYPES OF MASSAGE IN THE FIRST PERIOD OF DEVELOPMENT OF DEEP THROMBOSIS VESSELS OF THE LOWER LIMB - A.P. Berezovskiy (Academy of Cognitive and Natural Sciences, 2010)
On the basis of results o f avto eksperymenta. the technology of the use of various prospects and receptions of massage is offered, with the purpose of acceleration of restoration processes after the total thrombosis of deep vessels of tower extremity.